Modelagem matemática de um quadrotor - Medke, Renan (Universidade Federal do Pampa, 2016)
The work of mathematical modeling of a quadrotor aims to understand the functioning of a quadrotor, showing a detail from its coordinate transformations to obtain the equations describing their movements in three-dimensional plane. These equations are used in simulations where a movement is expected intuitively and then it was proven by means of the trajectory obtained in the simulation.
Keywords: Electrical engineering; Mathematical modeling; Unmanned aircraft systems; Engenharia elétrica; Modelagem matemática; Quadrotor; CNPQ::ENGENHARIAS